Air-fuel mixing and combustion behavior of gasoline-ethanol blends in a GDI wall-guided turbocharged multi-cylinder optical engine. (October 2016) - Catapano, Francesco; Sementa, Paolo; Vaglieco, Bianca Maria
Abstract: The investigation of phenomena involved in gasoline direct injection 4-stroke, 4-cylinder, optically-accessible engine were carried out at part load and speed condition with different ethanol-gasoline blends. The influence of injection pressure on ethanol addition, at percentages of 10%, 50% and 85%, was investigated by conventional and optical diagnostics. Combustion characteristics, such as mass fraction burned, heat release rate and combustion duration were calculated based on in-cylinder pressure curve data, Emissions of UHC, NOX, CO, CO2, and PM were measured. The injection and combustion phase by high spatial and temporal optical measurements were characterized. The spray penetration, and the flame structure and propagation speed were obtained by optical data. The addition of ethanol in gasoline allowed an improvement of engine performance in terms of IMEP and COVIMEP and emissions. In particular, for E50 the better performance was obtained thanks to an earlier vaporization during the injection and a spray almost compact with a higher penetration especially at 100 bar, that avoided the formation of liquid fuel deposits on the piston and subsequently pollutants in the exhaust. Meanwhile, for E85 the spray was characterized by a slower vaporization that created a less homogeneous charge and reduction of the flame front propagation in the late propagation phase. This allows a faster and more efficient combustion with respect to fuels characterized by high gasoline fraction. Finally, E85 and E50 showed higher values of the integral flame luminosity in the first phase of combustion due to the higher flame speed with respect to gasoline one. Moreover, the chemiluminescence imaging confirmed a lower number of diffusive flames with respect gasoline and E10 in the late combustion phase, when the flame burns the fuel film on the piston crown. These results validated the lower emission of UHC and smoke of E50 and E85 with respect to gasoline and E10. Highlights: Ethanol fuel used was obtained by renewable energy source of grape pomace. High ethanol blends improve performances IMEP COV and flame speed reduce UHC and soot emission. Flash-boiling strongly affects charge formation and structural behavior of sprays. E50 experiences fastest vaporization due to its peculiar evaporating properties. E85 spray shows a more defined boundary indicating the slowest vaporization.